(untitled) (Research, Society and Development, 2021)
The aim of this study was to investigate the effect of previous exposure to CsA on the expression of RANK and bone loss in experimental periodontitis induced in rats. Forty rats were divided into four groups as follows: Control (CON); Cyclosporine A (CsA), with daily doses of 10 mg/Kg of CsA; Ligature (LIG), with a ligature around the upper right second molar on day 30; and Ligature + CsA (CsAL). Sixty days later, the animals were sacrificed and samples removed for histomorphometric and immunohistochemical analysis of bone resorption, bone density and RANK expression. There was no significant influence of bone resorption on the application of CsA. LIG Group (735.88 ± 121.82) had significantly higher bone resorption (p = 0.01) than CON Group (569.13 ± 89.76), and CsAL Group (759.38 ± 198.23) also had significantly higher bone resorption (P = 0.001) than CsA Group (410.90 ± 105.95). Bone density in the CsA Group (87.49 ± 4.07) was lower than that of CON Group (92.42 ± 2.27) and similar to that of LIG Group (91.85 ± 3.91). CsAL Group (79.41 ± 3.81) showed the lowest density compared to the other groups. RANK did not differ between the groups. The prior exposure to CsA had no influence on the expression of RANK or bone resorption.